Oral Health and Diabetes: A Critical Partnership in Patient Care - Mohd Said, Shahida binti (International Journal of Human and Health Sciences (IJHHS), 2024)
Oral health and diabetes mellitus are two interconnected areas that require a collaborative patient care approach for enhanced treatment outcomes and quality of life. Diabetes has a profound effect on oral health and has periodontitis as its acknowledged complication. While poor oral hygiene, oral infections, and severe periodontitis can worsen diabetes outcomes. A comprehensive assessment of patients’ health and oral health status is fundamental in formulating a successful treatment approach that will benefit the patients both in dental and health settings. Furthermore, there is a growing concern about the significant association of periodontitis severity with diabetes presence and status as a comorbidity; more teeth can be saved and retained functionally in the mouth for the patients if identified and treated timely. Early detection of oral health problems in health clinics can improve the symptoms of oral diseases of patients with diabetes and the glycaemic status of periodontitis patients with diabetes risks in dental clinics. This session will share some experiences from the team on the integrated management strategies between dental and health professionals that may inspire other efforts towards the shared care of periodontitis and diabetes patients, particularly in the primary care settings. Innovative programmes involving smart partnerships with the industry and community will also be shared through this session. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S19